Physical activity of elderly people - Katarzyna Korabiusz; Agata Wawryków; Anna Fabian-Danielewska; Agnieszka Wilczyńska; Inga Janik; Mirela Niedzielska; Martyna Maciejewska; Monika Stecko (Kazimierz Wielki University, 2018)
Introduction: Ageing process is recognized as one of the most important aspects of XXI century. Most often it is considered from economical and social perspective however this dissertation's goal is to determine the effect of physical activity on the quality of life of elderly people, because age appropriate physical activity is the best way to stay healthy. Research goal: Goal of this dissertation is a review of literature about physical activity on of elderly people . Conclusion: Physical activity has a very significant effect on increasing the quality of life of elderly people